PENGARUH EKSTRAK KELENJAR HIPOFISA AYAM BROILER DALAM MEMPERCEPAT RESPON OVULASI IKAN KOI Cyprinus carpio L. - Mardhatillah, Hidayah; Efrizal, Efrizal; Rahayu, Resti (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p05, 2018)
This study aimed to determine the effect of broiler chicken pituitary gland extract and its best dosage in speeding up the ovulation response by means the latent period, the latest stage of egg maturation and the egg diameter of koi fish. This research was conducted with an experimental method in a completely randomized design (CRD) consisting of four treatments and three replications. The treatments were the injection without broiler pituitary extract (control) and with broiler pituitary extract 500 mg/kg, 600 mg/kg, 700 mg/kg body weight. As many as 12 individuals of female koi weighted 600-800 grams were used. The result demonstrated that the koi latency time after the injection ranged between 6-10 hours in experimental groups and 31 hours in control group. The maturity of eggs increased by 30 to 43.83%. The diameter of eggs increased by 0.06 to 0.10 mm in experimental groups and 0.02 mm in control  group.  It is concluded that the  injection of broiler pituitary extract caused a significantly different effect in speeding up the latency time as well as increasing the maturity of the final stages and diameter of eggs of koi fish with 500 mg/kg body weight as the best dosage.